Cardiac troponin T in coronary heart disease patients with chronic heart failure - V. S. Nikiforov; A. I. Karpishchenko; A. S. Svistov; V. L. Pastushenkov; E. A. Lobanova (Российский кардиологический журнал, 2005)
The study included 45 patients with coronary heart disease (CHD) and chronic heart failure (CHF) of functional class I-IV. Increased cardiac troponin T(cTnT) level could be used in verification and assessment of CHF decompensation severity. In CHF, increase in cTnT level was influenced by CHF decompensation, left ventricular systolic dysfunction and remodeling. At the same time, essential arterial hypertension, post-infarctial cardiosclerosis, permanent atrial fibrillation, left ventricular diastolic dysfunction, left atrium pathologic remodeling did not significantly influence cTnT concentration in patients with CHD and CHF.